Cultivating Students’ Critical Thinking and Collaboration: Literacy Practice in Digital Storytelling Project - Mardiana, Wiwik; Alivi, Justsinta Sindi; Krisdiana, Amy; Susanti, Ika (General English Education, 2025)
This research explores how a teacher’s literacy practices, through a digital storytelling project, foster critical thinking and collaboration among students. It also examines students' experiences during literacy activities and the project itself. Conducted as a qualitative case study, this research involved thirty-six senior high school students. Data were gathered through classroom observations, interviews, and documentation of students’ project artifacts. The findings suggest that using reading journals during self-directed reading at home promotes critical thinking and assists students in generating ideas for their digital storytelling projects. Besides, digital storytelling projects also play a key role in enhancing students’ critical thinking and collaboration skills. Students effectively articulated issues and proposed solutions within their stories. Some topics related to the environments chosen cover air pollution, water pollution, building/housing, and illegal logging. Participation in the collaborative project encouraged students to take responsibility for their contributions and to respect differing opinions within their teams. Exploring students’ views as their reflection on experiencing literacy practices in digital storytelling projects also reveals the positive impacts on their English ability. This approach provides educators with a practical and innovative strategy to foster students’ skills, i.e. critical thinking and collaboration in the 21st century in an educational context.